A new convergent synthesis of (±)‐methyl jasmonate based on a C4 + C6 synthon approach. (31st May 2017) - Jaunky, Piotr; Buirey, Julien; Mahaim, Cyril
Abstract: A new, convergent synthesis of (±)‐methyl jasmonate is presented. The strategy is based on a C4+C6 synthon approach. The C4 fragment N, 4, 4‐trimethoxy‐N‐methyl‐butanamide (5 ) was prepared in 4 steps starting from chloroacetyl chloride via the previously unreported N, 4, 4‐trimethoxy‐N‐methylbut‐2‐enamide (4 ). The coupling of5 with the C6 synthon, cis ‐3‐hexenyl magnesium chloride (6 ), provided easy access to ( Z )‐4‐oxodec‐7‐enal (8 ). The latter was converted to the key intermediate ( Z )‐2‐(pent‐2‐en‐1‐yl)cyclopent‐2‐en‐1‐one (9 ) from which (±)‐methyl jasmonate can be obtained in high yield using well‐established procedures. Abstract : A new, convergent synthesis of (±)‐methyl jasmonate is presented. The strategy is based on a C4 + C6 synthon approach. The C4 fragment (5) was prepared in 4 steps starting from chloroacetyl chloride. The coupling of 5 with the C6 synthon, cis‐3‐hexenyl magnesium chloride (6), provided an easy access to (Z)‐4‐oxodec‐7‐enal. The latter was converted to the key intermediate (Z)‐2‐(pent‐2‐en‐1‐yl)cyclopent‐2‐en‐1‐one (9) from which (±)‐methyl jasmonate can be obtained in high yield by well established procedures.